2006
DOI: 10.1111/j.1365-2222.2006.02645.x
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of heat‐treated Lactobacillus rhamnosus GG prevents development of atopic dermatitis in NC/Nga mice

Abstract: These findings suggest that some components of heat-treated L. GG may have an ability to delay the onset and suppress the development of atopic dermatitis, probably through a strong induction of IL-10 in intestinal lymphoid organs and systemic levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
74
3
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 43 publications
7
74
3
1
Order By: Relevance
“…GG has been shown to adjust t he Th/Th2 balance and induce IL-10 product ion dur ing allergic responses (Pessi et al 2000;Sawada et al 2007;Ghadimi et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…GG has been shown to adjust t he Th/Th2 balance and induce IL-10 product ion dur ing allergic responses (Pessi et al 2000;Sawada et al 2007;Ghadimi et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Sawada et al reported that oral administration of heat-treated LAB (Lactobacillus rhamnosus GG) prevented the development of AD in NC/Nga mice, although there was no significant difference in the plasma total IgE level between the LAB administration group and the control group. They speculated that dermatitis in skin lesion and IgE level might not be regulated coincidentally and the LAB might drive dermatitis to normalize without regulating the IgE production in NC/Nga mice (34). On the other hand, Segawa et al reported that there was a high correlation between clinical score and serum total IgE level while oral administration of heat-treated LAB (Lactobacillus brevis SBC8803) significantly prevented the development of AD and serum total IgE elevation in NC/ Nga mice (35).…”
Section: Discussionmentioning
confidence: 99%
“…Some components of heat-treated LGG may have an ability to delay the onset and suppress the development of atopic dermatitis, probably through a strong induction of IL-10 in intestinal lymphoid organs and systemic levels. 40 After probiotic consumption, LGG, Lactobacillus rhamnosus GG; LL, Lactococcus lactis; IFN-g, interferon-g; TGF-b, transforming growth factor-b; TLR, Toll-like receptor; ", increase in symptoms or negative effect; #, decrease in symptoms or positive effect; 1 , no change in symptoms or no effect. …”
Section: R E T R a C T E Dmentioning
confidence: 99%